Synthesis and Analysis of 2-(2-Formyl-4-nitrophenoxy) Phenyl Palmitate - Sanchita (My University, 2023)
Diphenyl ethers are essential compounds due to their antibacterial characteristics and materialistic purposes. Many of these have been obtained from natural sources and have various roles in the pharmaceutical and material worlds. Diphenyl ethers with long chain hydrocarbons have wide range of applications in different areas. The work presented here describes the synthesis and analysis of compound 2-(2-formyl-4-nitrophenoxy) phenyl palmitate (CompoundG) starting from compound 2-Bromo-5-nitrobenzaldehyde (Compound-A). All the synthesized (compounds A-G) were characterized by 1H and 13C-NMR spectroscopy. A detailed analysis of both the compounds- E and G was done using HRMS data.
M.Sc. (Chemistry) Thesis of Sanchita
Keywords: Nitration; Nucleophilic Aromatic Substitution; Estrase; Liquid Crystal Property; Catachol